Sites of Memory of Atlantic Slavery in European Towns with an Excursus on the Caribbean - Schmieder, Ulrike (2018)
For a long time, the impact of Atlantic slavery on European societies was discussed in academic circles, but it was no part of national, regional and local histories. In the last three decades this has changed, at different rhythms in the former metropolises. The 150th anniversary of the abolition of slavery in France (1998) and the 200th anniversary of the prohibition of the slave trade in Great Britain (2007) opened the debates to the broader public. Museums and memorials were established, but they coexist with monuments to slave traders as benefactors of their town. In Spain and Portugal the process to include the remembrance of slavery in local and national history is developing more slowly, as the impact of slave trade on Spanish and Portuguese urbanization and industrialization is little known, and the legacies of recent fascist dictatorships are not yet overcome. This article focuses on sites of commemoration and silent traces of slavery.